Proceedings of the 30th ACM Conference on Hypertext and Social Media 2019
DOI: 10.1145/3342220.3344927
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Spread of Exaggerated Health News Content over Social Media

Abstract: categories like 'bio', 'health', 'body' and 'negative emotion' are more pronounced in the tweets posted by the users in the latter class. As a final step we use these observations as features and automatically classify the two groups achieving an F1-score of 0.83.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The association between death, funerals, and emotions or affective processes (Gortner and Pennebaker, 2003 ; Glasgow et al, 2014 ) led to the selection of affective processes for further evaluation. Previous studies also identified words expressing emotions or affect significantly that influence linguistic dimensions (Wardecker et al, 2017 ; Khalil et al, 2018 ; Patro et al, 2018 ). The present research aimed to explore the association between linguistic dimensions such as function, words, and affect.…”
Section: Methodsmentioning
confidence: 95%
“…The association between death, funerals, and emotions or affective processes (Gortner and Pennebaker, 2003 ; Glasgow et al, 2014 ) led to the selection of affective processes for further evaluation. Previous studies also identified words expressing emotions or affect significantly that influence linguistic dimensions (Wardecker et al, 2017 ; Khalil et al, 2018 ; Patro et al, 2018 ). The present research aimed to explore the association between linguistic dimensions such as function, words, and affect.…”
Section: Methodsmentioning
confidence: 95%
“…Exaggeration: Exaggeration can take different forms, such as the alteration of correlational statements into causal statements, change in explicitness and directness of included advice, or twisting of important experimental facts (Patro et al, 2018). Clickbait headlines are often modified to appear more negative than the actual article, exaggerate main points, or over-emphasize conflicts to attract more readers (Ecker et al, 2014).…”
Section: Data Representationmentioning
confidence: 99%
“…In the last two decades, there is a substantial increase in the number of publications in the domain of media manipulation and fake news [10], [11]. A number of tasks have been introduced since then such as fact checking [12]- [14], rumor detection [15], stance detection [16], assessing credibility [17], and exaggeration [18], [19]. Moreover, several datasets have been introduced for these tasks (see in particular the datasets on claim verification [16], [20]- [22], entire article verification [23] and verification of social media posts [24]- [26]).…”
Section: Related Workmentioning
confidence: 99%